Short-term trade dependencies of the South as an obstacle to degrowth? Quantifying the twin challenge of global dependencies - Claudius Gräbner-Radkowitsch; Birte Strunk (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2025)
This paper is a first attempt to quantify the potential short-term effects on income and business profits that may occur in the Global South if the Global North were to implement policies to reduce and relocalize consumption and production. To this end, we use the EORA26 global input-output table to calculate dependency shares, which capture the share of incomes and profits in the Global South that manifests because of trade with the Global North. In the aggregate, we find that roughly a seventh of total incomes and profits in the South depends on trade in the North, although dependency varies significantly by region. We find that most of this dependency stems from trade of intermediate goods, not from exports for final demand. We also find that there is no single factor beyond trade-openness that clearly explains the differences in dependency among countries in the South, pointing to the importance of country-specific analyses. We therefore argue that a deeper understanding of the specific trade relations of any given country in the Global South with countries of the North is necessary for researchers interested in post-growth industrial policy as well as, more broadly, any type of policy-driven degrowth transitions in the Global North.
Keywords: 330; degrowth; unequal exchange; structural dependencies; input-output analysis; Global North; Global South; trade; delinking; decolonization